Dihydrochalcone-derived polyphenols from tea crab apple (Malus hupehensis) and their inhibitory effects on α-glucosidase in vitro. Issue 5 (9th May 2019) - Lv, Qiuyue; Lin, Yushan; Tan, Zhexu; Jiang, Baoping; Xu, Lijia; Ren, Haiqin; Tai, William Chi-shing; Chan, Chi-on; Lee, Chi-sing; Gu, Zhengbing; Mok, Daniel K. W.; Chen, Sibao
Abstract : α-Glucosidase inhibitory agents with unique carbon skeletons from tea crab apple ( Malus hupehensis ). Abstract : Three dihydrochalcone-derived polyphenols, huperolides A–C (1–3 ), along with thirteen known compounds (4–16 ) were isolated from the leaves of Malus hupehensis, the well-known tea crab apple in China. Their chemical structures were elucidated by extensive spectroscopic analysis including NMR (HSQC, HMBC, 1H–1H COSY and ROESY), HRMS and CD spectra. Huperolide A is a polyphenol with a new type of carbon skeleton, while huperolides B and C are a couple of atropisomers, which were isolated from natural sources for the first time. The antihyperglycemic effects of the isolated compounds were evaluated based on assaying their inhibitory activities against α-glucosidase. As a result, phlorizin (4 ), 3-hydroxyphloridzin (5 ), 3- O -coumaroylquinic acid (12 ) and β-hydroxypropiovanillone (15 ) showed significant concentration-dependent inhibitory effects on α-glucosidase. Therefore, those compounds might be responsible for the antihyperglycemic effect of this herb, and are the most promising compounds to lead discovery of drugs against diabetes.